Measuring and reporting intellectual capital in Malaysian local authorities - Kamaluddin, Amrizah; Huang, Ching Choo; Ahmad Noruddin @ Nordin, Nur Adura; Baharum, Zafiruddin (2012)
Non-public or private sector has given much attention to the management and reporting of intellectual capital over the last few decades. It was claimed that in the knowledge-based economy, corporate value lies not only in the tangible assets but in the intangibles or intellectual capital comprising skills and knowledge of employees, customer relationships, etc. (Huang et aI., 2010). This main objective of this study is to identify the intellectual capital indicators which are useful to local authorities and make a comparison with the indicators currently used by managers in local authorities. A total of 280 copies of questionnaires were distributed to the district officers and officers of the Malaysian local authorities. Total of 73 officers who works in Malaysian local authorities participate as respondents in this paper. Factor analysis and multiple regression were used for data analysis. The results of the study provide significant evidences on the role of relational capital and structural capital in the local authorities of a developing nation like Malaysia.